2011
DOI: 10.1073/pnas.1117099109
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose synthase activity in the sus1/sus2/sus3/sus4 Arabidopsis mutant is sufficient to support normal cellulose and starch production

Abstract: Sucrose synthase (SUS) catalyzes the reversible conversion of sucrose and a nucleoside diphosphate into the corresponding nucleoside diphosphate-glucose and fructose. In Arabidopsis , a multigene family encodes six SUS (SUS1-6) isoforms. The involvement of SUS in the synthesis of UDP-glucose and ADP-glucose linked to Arabidopsis cellulose and starch biosynthesis, respectively, has been questioned by Barratt et al. [(2009) Proc Natl Acad Sci USA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 61 publications
(71 reference statements)
7
132
0
1
Order By: Relevance
“…One of the most significantly DEGs in primary carbohydrate metabolism in the array data set is SUS4, encoding a SUCROSE SYNTHASE that participates in Suc breakdown, in particular under low oxygen stress (Baroja-Fernández et al, 2012;Pucciariello et al, 2012). Validation of these results by RT-qPCR studies revealed that SUS4 expression is partially impaired in the bzip1 bzip53 mutant ( Figure 3C).…”
Section: Transcriptomic Analyses Reveal Functions Of Bzip1 and Bzip53mentioning
confidence: 55%
See 1 more Smart Citation
“…One of the most significantly DEGs in primary carbohydrate metabolism in the array data set is SUS4, encoding a SUCROSE SYNTHASE that participates in Suc breakdown, in particular under low oxygen stress (Baroja-Fernández et al, 2012;Pucciariello et al, 2012). Validation of these results by RT-qPCR studies revealed that SUS4 expression is partially impaired in the bzip1 bzip53 mutant ( Figure 3C).…”
Section: Transcriptomic Analyses Reveal Functions Of Bzip1 and Bzip53mentioning
confidence: 55%
“…In particular, regulation of the hypoxia marker gene SUS4, encoding a Sucdegrading enzyme (Baroja-Fernández et al, 2012), depends on bZIP1/ bZIP53, which might explain the increase in monosaccharides 3 to 6 h after the onset of stress. In the same time span, Suc levels highly increase in the bzip1 bzip53 mutant, presumably because Suc is not degraded to hexoses, as occurs in the wild type.…”
Section: Bzip1 and Bzip53 Reprogram Primary Carbohydrate And Amino Acmentioning
confidence: 99%
“…SuSy has also been suggested to be involved, at least in part, in the sucrosestarch conversion process in autotrophic organs. 15,16 Earlier studies 17,18 have shown that different organs of the sus1/sus2/sus3/sus4 quadruple Arabidopsis mutant accumulate WT starch content. We employed the method for confocal fluorescence microscopic observation described in this work to visualize the starch granules in the chloroplasts of sus1/sus2/sus3/sus4 mutant.…”
mentioning
confidence: 99%
“…The UDPGlc is converted to adenosine 5'-diphosphate glucose (ADPGlc) in the cytosol by the stepwise reactions of UDPGlc pyrophosphorylase and ADPGlc pyrophosphorylase (AGPase), while the conversion of fructose to ADPGlc involves hexokinase, phosphoglucoisomerase and phosphoglucomutase [11]. Although UDP is the preferred nucleoside diphosphate substrate for SuSy, ADP could also be an acceptor molecule of this sucrolytic enzyme to produce ADPGlc [12][13][14]. Cytosolic ADPGlc is then thought to be transported into the amyloplast by means of Brittle-1, a membrane protein located in the envelope membranes of amyloplasts [15], whose absence results in reduced starch content [16,17].…”
Section: Sucrose Synthase (Susy)mentioning
confidence: 99%
“…It starts with individual chains as the first level, which are formed by ADP-glucose through (1→4)-α-glycosidic linkages. Those chains in amylopectin have been further denoted as C chains having the reducing end, A chains (degree of polymerization, DP, [6][7][8][9][10][11][12] carrying no branches, B1 chains (DP [13][14][15][16][17][18][19][20][21][22][23][24] carrying A chains, B2 chains (DP DOI 10.1515/amylase-2017-0006 [25][26][27][28][29][30][31][32][33][34][35][36] carrying B1 chains, B3 chains (DP > 36) carrying B2 chains, and so on (for a recent review, see [2]). Although still occasionally one finds statements to the contrary, amylose is not solely linear, but contains a small but significant number of long-chain branches [3].…”
Section: Introductionmentioning
confidence: 99%